New Insights Into the 2070calyrBP Pyroclastic Currents at El Misti Volcano (Peru) From Field Investigations, Satellite Imagery and Probabilistic Modeling - CHARBONNIER, SYLVAIN J.; THOURET, JEAN-CLAUDE; GUEUGNEAU, VALENTIN; CONSTANTINESCU, ROBERT (Frontiers in Earth Science, 2020)
Pyroclastic currents (PCs) are the most challenging volcanic hazards for disaster planners in populated areas around volcanoes. “El Misti” volcano (5,825 m above sea level), located only 17 km from the city center of Arequipa (>1.1 million inhabitants), South Peru, has produced small-to-moderate volume (<1 km3) PCs with a frequency of 2,000–4,000 years over the past 50 kyr. The most recent Plinian eruption dated at 2070 cal yr BP (VEI 4) has been selected as one of the reference events for the hazard assessment and risk mitigation plan of Arequipa. Associated pumice- and lithic-rich PC deposits were emplaced from at least four phases of column-collapse into the radial valleys draining the volcano as far as 13 km toward the city. Field mapping and stratigraphic surveys conducted in seven valleys affected by the 2070 cal yr BP PCs were combined with a new high-resolution (2 m) digital surface model of the volcano to better estimate the distribution of individual PC volumes. Such data acquisition is particularly critical for two of these valleys (San Lázaro and Huarangal-Mariano Melgar) for which the medial and distal reaches now cross the suburbs of Arequipa. The total area covered by the PC deposits is estimated at 141 km2 for a total bulk volume estimated at 406 ± 140 × 106 m3. These volumes were used as input parameters to better calibrate probabilistic numerical simulations of future similar PC events using the two-layer VolcFlow model and assess the impacts of both the concentrated and dilute portions of these currents in the San Lázaro and Huarangal valleys. We discuss probability values of PC inundation obtained from these simulations both in terms of their implications for the dynamics of such hazardous PCs at El Misti and for their integration into its current multi-hazard assessment. Modeling results demonstrate that the risk of overbank processes and spreading of unconfined PCs inside Arequipa should be refined. This multi-disciplinary study aims to help the civil authorities’ understanding of the likely effects of PCs associated with a similar VEI 4 eruption of El Misti on the urban area of Arequipa.